THE EFFECT OF OPERATING CASH FLOW AND COMPANY GROWTH ON STOCK PRICES: (Empirical study on Food and Beverage Subsector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2016-2020) - Lerika Br Simarmata; Intan Rahma Sari (Transpublika Publisher, 2022)
This study aims to determine the effect of operating cash flow and company growth on stock prices in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The population of this study are manufacturing companies in the food and beverage sub-sector which are listed on the Indonesia Stock Exchange in 2016-2020. The sampling technique used was purpose sampling and the research data obtained were 11 companies with 5 years of research so that the number of samples in this study was 55 company data. The data analysis method used is panel data regression. The results showed that partially operating cash flow had a significant effect on stock prices, while company growth had no significant effect on stock prices. Meanwhile, simultaneously operating cash flow and company growth had a significant effect on stock prices.